Relationship between Patient Readiness for Hospital Discharge and Post-Discharge Outcomes” - Asadi, Nasim; Keshavarzi, Saleh; Kamyari, Naser; Vatandost, Salam (Advances in Nursing & Midwifery, 2023)
Abstract Introduction: The degree of patient readiness for discharge can be one of the important and influential factors in the outcomes of the post-discharge process. The purpose of this study is to determine the Relationship between Patient Readiness for Hospital Discharge and Post-Discharge Outcomes. Methods: The study is descriptive-correlational. Through convenient sampling 351 hospitalized patients in general wards were selected. The data collection procedure was done by using the Readiness for Hospital Discharge Scale (RHDS), and research made post-discharge follow-up form. RHDS contain 8 items that measure 4 dimensions and in analysis mean score and standard deviation in the range of 0 to 10 reported. The post-discharge follow-up form includes 6 items with yes/no answers. There was not any restriction on the number of outcomes for each individual These items are related to possible and unforeseen consequences of one month after the patient’s discharge from the hospital. Readiness for discharge as self-reported and its related outcomes were assessed by telephone communication 30 days after discharge. Collected data were analyzed by using SPSS version 21.0 at a significance level of 0.05. Results: The total score of readiness for hospital discharge scale (RHDS), was at a high level (7.82 ± 1.17). The mean score for readiness for hospital discharge had a significant relationship with the recovery outcomes (0.028), readmission (0.001), and death (0.005). Conclusions: The results of the study showed to reduce the negative outcomes of hospital discharge, the patient’s assessment of his condition at the time of discharge should be taken into consideration.